2021
DOI: 10.1016/s2213-8587(21)00139-x
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib therapy for patients with recent-onset type 1 diabetes: a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial

Abstract: Background Type 1 diabetes results from autoimmune-mediated destruction of β cells. The tyrosine kinase inhibitor imatinib might affect relevant immunological and metabolic pathways, and preclinical studies show that it reverses and prevents diabetes. Our aim was to evaluate the safety and efficacy of imatinib in preserving β-cell function in patients with recent-onset type 1 diabetes. MethodsWe did a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Patients with recentonset type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 35 publications
(71 reference statements)
0
43
0
1
Order By: Relevance
“…For instance, β cells experience unmitigated endoplasmic reticulum (ER) stress and activate the terminal unfolded protein response (UPR) leading to apoptosis during the development of T1D [ 4 ]. Small molecule therapeutics that block terminal UPR have shown promise in clinical trials of new onset T1D patients by slowing the decline in C-peptide production after diagnosis [ 5 , 6 ]. Thus, clinical interventions to target β cell stress responses are emerging as a therapeutic strategy for T1D.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, β cells experience unmitigated endoplasmic reticulum (ER) stress and activate the terminal unfolded protein response (UPR) leading to apoptosis during the development of T1D [ 4 ]. Small molecule therapeutics that block terminal UPR have shown promise in clinical trials of new onset T1D patients by slowing the decline in C-peptide production after diagnosis [ 5 , 6 ]. Thus, clinical interventions to target β cell stress responses are emerging as a therapeutic strategy for T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinases are important signaling cascade mediators, playing critical roles in a variety of biological processes such as growth, differentiation, apoptosis, and metabolism in response to internal and external stimuli. It is worth noting that imatinib, a tyrosine kinase inhibitor, was shown in a multicenter, randomized, double-blind, placebo-controlled, phase 2 trial to preserve beta-cell function in patients with recent-onset T1D ( 26 ). Possible mechanisms of imatinib might include, 1) inhibiting ABL-IRE1α interaction and dampening IRE1α RNase hyperactivity, thus resulting in the reduction of pancreatic β cell apoptosis as demonstrated in a non-obese diabetic (NOD) mouse study ( 27 ); 2) preventing the process of T cell and macrophage infiltration into islets ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…By blunting IRE1a RNase hyperactivity, imatinib reduces beta-cell apoptosis and preserves physiological function. In humans, a clinical trial found imatinib preserved beta-cell function at 12 months in adults with recent-onset T1D (195). Ongoing studies will investigate dose and duration of therapy as well as safety and efficacy for use in children.…”
Section: Modulation Of Er-induced Beta-cell Deathmentioning
confidence: 99%
“…An ongoing clinical trial using imatinib mesylate (brand name Gleevec), a tyrosine kinase inhibitor, shows promising results in targeting beta-cell ER stress (195). The efficacy of imatinib for the treatment of various immune-mediated diseases is currently being tested.…”
Section: Modulation Of Er-induced Beta-cell Deathmentioning
confidence: 99%